Model Problem Based Learning Berbantuan Diorama Bulusan Untuk Meningkatkan Hasil Belajar Siswa Kelas IV - Lestari, Santi; Masfuah, Siti; Oktavianti, Ika (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This study aims to describe the increase in student learning outcomes on theme 7 class IV SD 4 Hadipolo through the Problem Based Learning model assisted by Bulusan dio-rama. This type of research is Classroom Action Research. The research subjects were 25 students in grade IV SD 4 Hadipolo for the 2021/2022 academic year. Data collection techniques include interviews, observations, tests, and documentation. Quantitative and qualitative data analysis. The results showed an increase in learning outcomes in the knowledge aspect of pre-cycle science content by 56%, increasing by 68% in cycle I and 84% in cycle II. The pre-cycle Indonesian content achieved 60% classical learning mastery, increased by 72% in cycle I and increased by 88% in cycle II. There was an increase in the results of the observation of the pre-cycle students' skills from 63.6 to 74.64 in the first cycle, an increase of 85.03 in the second cycle. Based on the results of the study it can be concluded that the application of the Problem Based Learning model assisted by the Bulusan diorama can improve student learning outcomes in theme 7 class IV SD 4 Hadipolo.